STUDY OF CONVEXITY IN SETS AND FUZZY SETS - Abubakar Abdulkarim; Mukaila, I. F. (FUDMA JOURNAL OF SCIENCES, 2022)
In this paper, we present an overview of both classical and fuzzy convexity, particularly, in conjunction with continuity5 and some topological concepts, and provide proofs of some of their algebraic properties along with suitable illustrations. We have extended the work of (Ammar E. E., 1999) by proving that if and are two convex fuzzy sets, then , , , and are also convex fuzzy sets. We have also shown that the convexity of a fuzzy set implies semistrict quasi-convexity